Exploiting provisions of land economic productivity without degrading its natural capital. (January 2015) - Nkonya, Ephraim; Anderson, Weston
Abstract: Motivated by the United Nations target of achieving zero net land degradation by 2030 and the Rio + 20 United Nations' "future we want" resolution, which aims to achieve a green economy, this study was conducted with an objective of identifying strategies for achieving sustainable use of lands at a global and a regional level. Using econometric approaches, we observed that achievement of zero net degradation is possible, even in developing regions, if land users are provided with good market access and secure land rights and if institutions are strengthened to regulate land use. Such achievement is possible, even in densely populated and severely impoverished areas. The probability of achieving zero net land degradation is greater in drylands – especially among communities with pastoral and other livestock-based livelihoods. Highlights: Zero net land degradation is achievable even in poor countries but require better investment & policies. Access to markets & governance increase the likelihood to achieve sustainable land management (SLM). Agricultural intensification increases the probability of achieving SLM in many areas. Poverty and high population density are associated with greater propensity to achieve SLM. Drylands & cattle density have greater potential to achieve SLM but public investment is limited.